2021
DOI: 10.1109/tnsre.2021.3078460
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Emotional Sensitivity Using fNIRS Based Dynamic Functional Connectivity

Abstract: In this study, we proposed an analytical framework to identify dynamic task-based functional connectivity (FC) features as new biomarkers of emotional sensitivity in nursing students, by using a combination of unsupervised and supervised machine learning techniques. The dynamic FC was measured by functional Near-Infrared Spectroscopy (fNIRS), and computed using a sliding window correlation (SWC) analysis. A k-means clustering technique was applied to derive four recurring connectivity states. The states were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 65 publications
(70 reference statements)
0
17
0
Order By: Relevance
“…Notably, dynamic functional connectivity analyses also suggested that functional couplings (FCs) within prefrontal cortex including IFG, OFC, dlPFC and mPFC during the whole emotional inhibition task were significantly modulated by taVNS. This approach helps us quantify the experimental paradigm-based variations of brain functional networks affected by taVNS regardless of conditions (Tang et al ., 2021; Lu et al ., 2023). Among these couplings, taVNS significantly strengthened dlPFC-mPFC/ IFG/OFC/ dlPFC and OFC-IFG links in States1, 3 and 4, suggesting that such dlPFC- and OFC-related functional couplings played primary role in taVNS effects on emotional inhibitory processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, dynamic functional connectivity analyses also suggested that functional couplings (FCs) within prefrontal cortex including IFG, OFC, dlPFC and mPFC during the whole emotional inhibition task were significantly modulated by taVNS. This approach helps us quantify the experimental paradigm-based variations of brain functional networks affected by taVNS regardless of conditions (Tang et al ., 2021; Lu et al ., 2023). Among these couplings, taVNS significantly strengthened dlPFC-mPFC/ IFG/OFC/ dlPFC and OFC-IFG links in States1, 3 and 4, suggesting that such dlPFC- and OFC-related functional couplings played primary role in taVNS effects on emotional inhibitory processes.…”
Section: Discussionmentioning
confidence: 99%
“…This approach helps us quantify the experimental paradigm-based variations of brain functional networks affected by taVNS regardless of conditions (Tang et al, 2021;Lu et al, 2023). Among these couplings, taVNS significantly strengthened dlPFC-mPFC/ IFG/OFC/ dlPFC and OFC-IFG links in States1, 3 and 4, suggesting that such dlPFC-and OFC-related functional couplings played primary role in taVNS effects on emotional inhibitory processes.…”
Section: Discussionmentioning
confidence: 99%
“…Coping with stressors often involves finding ways to manage and reduce the stress and anxiety they create through techniques such as time management, relaxation, or seeking support from others. In a study [72] the subjects had to perform mental arithmetic, auditory monitoring, visual monitoring, and phone number entry tasks all at the same time and separately to observe the different outcomes [70], [76], To mitigate the impact of the order, participants were randomly allocated to different sessions, with 50% experiencing the affective stimuli during one instance [75],Figure 3 shows some of the most commonly used decision-making tasks.…”
Section: Stressors and Decision-making Tasksmentioning
confidence: 99%
“…The baby rhythm song belongs to empathizing and is known for its calming qualities, whereas pop-punk is classified as systemizing because of its intense character [106]. Ten sound clips from the International Affective Digitized Sounds system (IADS) that were emotionally evocative (negative valence: 2.147 0.473; high arousal: 7.388 0.494) were presented alongside ten neutral sound clips in [75].…”
Section: ) Music Taskmentioning
confidence: 99%
“…Compared with the commonly used resting-state experiment, walking could promote more valuable signals of PD patients since gait disorder is common among PD patients and is considered as one of the primary disabling symptoms [28], [29]. Dynamic functional connectivity considers the temporal variations of brain networks and could capture the meaningful changes during walking [30], [31], [32], [33]. The dynamics of the brain are impacted by PD, which may lead to the deterioration of brain information transmission during walking [34], [35], [36].…”
Section: Introductionmentioning
confidence: 99%